Prosthodontic and comprehensive treatment of temporomandibular disorders - Andreas, Andreas; Aidilla, Dara; Chairunnisa, Ricca (Indonesia Prosthodontic Association, 2021)
Temporomandibular disorder (TMD) is the common term used to describe a range of disorder affecting the temporomandibular joint (TMJ). Facial pain is a common symptom that patients present to their dentist, and TMDs represent a significant proportion of the non-dental causes of this pain. These disorders can have a profound effect on a patient’s quality of life. The management goals for the prosthodontist are patient comfortable, occlusal stability and the complex restoration of the teeth.